1995
DOI: 10.1164/ajrccm.151.5.7735615
|View full text |Cite
|
Sign up to set email alerts
|

Ciliary defects in healthy subjects, bronchiectasis, and primary ciliary dyskinesia.

Abstract: To develop criteria to aid in the diagnosis of primary ciliary dyskinesia (PCD) we analyzed quantitatively the incidence and the range of ciliary ultrastructural abnormalities in healthy subjects and in patients with respiratory tract disease. The beat frequency and ultrastructure of nasal respiratory tract cilia, including ciliary orientation, were measured in 62 healthy subjects (31 nonsmokers, 20 exsmokers, and 11 smokers), ranging in age from 1 to 76 yr, and in 51 patients with respiratory tract disease. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
95
0
8

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(106 citation statements)
references
References 13 publications
3
95
0
8
Order By: Relevance
“…Ciliary ultrastructure results were expressed as a percentage of abnormal cilia among the total number of cilia analysed. As previously reported, up to 10% of cilia in control specimens can exhibit ultrastructural defects [10,11]. For this study, ciliary abnormalities were defined as the presence of .20% of ciliary defects.…”
Section: Ciliary Ultrastructurementioning
confidence: 91%
See 1 more Smart Citation
“…Ciliary ultrastructure results were expressed as a percentage of abnormal cilia among the total number of cilia analysed. As previously reported, up to 10% of cilia in control specimens can exhibit ultrastructural defects [10,11]. For this study, ciliary abnormalities were defined as the presence of .20% of ciliary defects.…”
Section: Ciliary Ultrastructurementioning
confidence: 91%
“…Since 2002, for questionable IDA in micrographs obtained by TEM, computerised analysis of cilia was systematically performed to improve IDA visualisation, as previously reported [12]. Ciliary orientation was systematically evaluated by comparing the position of the central pairs of adjoining cilia as previously described [11,13]. Disorientation was defined as an angle .25u.…”
Section: Ciliary Ultrastructurementioning
confidence: 99%
“…This difference was only apparent when compared with a matched control group, as the normal range of CBF showed a wide age-related spread. 11,24,25 The greater pre-HSCT respiratory compromise may partly be owing to the inclusion of more acute leukemia and lymphoma cases, with more intensive chemotherapy exposure. 26 Our results also showed reduced CBF after HSCT, regardless of GVHD occurrence and its treatment, but failed to show significant correlation with respiratory compromise.…”
Section: Discussionmentioning
confidence: 99%
“…These include complete absence or deficiency of outer or inner dynein arms, nexin links, radial spokes, central sheath, inner microtubules, and even the entire axoneme. [20][21][22] The significance of isolated ciliary ultrastructural abnormalities without functional deficit is, however, debatable. 23 Our study showed, for the first time, that allogeneic BMT was associated with ciliary dysfunction, especially for patients suffering from GVHD and BO.…”
Section: Discussionmentioning
confidence: 99%
“…The difference was also apparent when compared with a matched control group, since the normal range of CBF extended over a wide range, and a significant overlap occurs between normal and abnormal values. 21,24 On the other hand, CBF abnormalities in BO patients after lung transplantation have been extensively studied. Transient reversible ciliary dysfunction occurs in all patients who have had lung transplantation.…”
Section: Discussionmentioning
confidence: 99%